The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/ijcs.12110
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of financial factors, resources and skills in predicting food security status among college students

Abstract: The prevalence of food insecurity among college students has received little attention in academic literature, despite previous studies suggesting increased risk and potentially high rates of food insecurity among students. Additionally, the combined effects of financial and food management skills and resources have not been considered when examining student food security. A sample of 557 undergraduate students at a large, public university in the southeastern United States was surveyed to assess food security… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
192
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(226 citation statements)
references
References 28 publications
16
192
4
Order By: Relevance
“…Others have shown that health disparities are prevalent in college populations; 13, 14 however, very few studies have been conducted on food insecurity in U.S. college students. 15,16 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have shown that health disparities are prevalent in college populations; 13, 14 however, very few studies have been conducted on food insecurity in U.S. college students. 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…For example, food insecurity has been shown to be 1.5 times higher among Black and Hispanic students compared to White or Asian students. 17 Food insecure students were more likely to receive financial aid, 15 not live with family, 14, 18, 19 to have jobs while taking classes, 17, 19 and to have lower grades. 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that women empowerment was associated with better intake of calories and dietary diversity. Through a survey conducted among university students, Gaines et al (2014) proved the importance of financial status, resources and skill development, and described them as food resource adequacy. Similar results were found in Nigeria by Titus and Adetokunbo (2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been also suggested that low income is an important determinant of food insecurity. While families with food insecurity are not necessarily poor, other demographic and socioeconomic factors may be associated with the increased risk of food insecurity, including unemployment, limited access to food aid programs, low level of education, drug and tobacco abuse, and heavy costs of housing, transportation, and healthcare (12,13).…”
Section: Introductionmentioning
confidence: 99%